Comparative dosimetric study of radiotherapy in high-grade gliomas based on the guidelines of EORTC and NRG-2019 target delineation - Yan, Ouying; Teng, Haibo; Jiang, Cuihong; He, Lili; Xiao, Shuai; Li, Yanxian; Wu, Wenqiong; Zhao, Qi; Ye, Xu; Liu, Wen; Fan, Changgen; Wu, Xiangwei; et al. (Frontiers in Oncology, 2023)
Purpose: Radiotherapy is one of the most important treatments for high-grade glioma (HGG), but the best way to delineate the target areas for radiotherapy remains controversial, so our aim was to compare the dosimetric differences in radiation treatment plans generated based on the European Organization for Research and Treatment of Cancer (EORTC) and National Research Group consensus (NRG) to provide evidence for optimal target delineation for HGG. Methods: We prospectively enrolled 13 patients with a confirmed high-grade glioma from our hospital and assessed dosimetric differences in radiotherapy treatment plans generated according to the EORTC and NRG-2019 guidelines. For each patient, two treatment plans were generated. Dosimetric parameters were compared by dose-volume histograms for each plan. Results: The median volume for planning target volume (PTV) of EORTC plans, PTV1 of NRG-2019 plans, PTV2 of NRG-2019 plans were 336.6 cm3 (range 161.1-511.5 cm3), 365.3 cm3 (range 123.4-535.0 cm3), and 263.2 cm3 (range 116.8-497.7 cm3), respectively. Both treatment plans were found to have similar efficiency and evaluated as acceptable for patient treatment. Both treatment plans showed well conformal index and homogeneity index and were not statistically significantly different (P = 0.397, P = 0.427, respectively). There was no significant difference in the volume percent of brain irradiated to 30Gy, 46Gy, and 60Gy according to different target delineations (P = 0.397, P = 0.590 and P = 0.739, respectively). These two plans also showed no significant differences in the doses to the brainstem, optic chiasm, optic nerve, lens, eyes, pituitary, and temporal lobes (P = 0.858, P = 0.858, 0.701, P = 0.794, P = 0.701, P = 0.427, P = 0.489, P = 0.898, P = 0.626, P = 0.942 and P = 0.161, respectively). Conclusion: The NRG-2019 project did not increase the dose of organs at risk (OARs) radiation. This is a significant finding that further lays the groundwork for the application of the NRG-2019 consensus in the treatment of patients with high-grade gliomas.